The practice of autonomous learning among Arabic language learners in CELPAD - Che Haron, Sueraya (s.n, 2012)
This study investigated the practice of autonomy in Arabic language learning among Arabic language learners at the International Islamic University Malaysia. In other words they have the capabilities to take charge of their own learning except in several items especially when it comes to self-productive activities such as: communication, writing and translation